Medicine in an age of commerce and empire Britain and its tropical colonies, 1660-1830 - Harrison, Mark, 1964- (Oxford University Press, 2010)
'Medicine in an Age of Commerce and Empire' explores the impact of commercial and imperial expansion on British medicine from the late 17th century to the early 19th century.